PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS HIGHER ORDER THINKING SKILLS PADA PEMBELAJARAN SOSIOLOGI - Rini Parmila Yanti (Jurnal Public Administration, Business and Rural Development Planning, 2022)
This study aims to produce student worksheets based on higher order thinking skills in Sociology learning for class X that meet valid and practical criteria. This type of research is development research. The development research model used is a 4-D development model, namely define, design, develop and disseminate. In this study, only up to the develop stage due to time constraints. This research was conducted with the material of Social Interaction. The research instruments include validity sheets and practicality sheets (teacher and student response questionnaires). In the validation process, the Student Worksheet is validated by 1 material expert, 1 linguist and 1 media expert. In the practical process, the Student Worksheet was tested by 2 teachers and 6 students. Based on the results of the study, the development of student worksheets based on higher order thinking skills in Sociology learning for class X resulted in meeting the very valid criteria with an assessment percentage of 93%, and meeting the very practical criteria with a percentage of 95.2%. So, it can be concluded that student worksheets based on higher order thinking skills in Sociology learning for class X are very valid and very practical to use as learning materials.